Modern electric, hybrid electric, and fuel cell vehicles - Ehsani, Mehrdad (Taylor & Francis, CRC Press, 2018)
his text delivers expanded and detailed coverage of the fundamentals, theory and design of electric, hybrid electric, and fuel cell vehicles.